Secondary hemophagocytic lymphohistiocytosis linked to pathogenic microorganisms in pediatrics, pathophysiology and diagnosis: A review. - Bermeo-Botero, Camila (2022)
Secondary hemophagocytic lymphohistiocytosis (s-HLH) is an acute systemic inflammatory disorder caused by uncontrolled activation of the immune system which produces a cytokine storm. This disorder is caused by infections, autoimmune diseases or malignancy and is more prevalent in adults, therefore it has few studies in pediatric patients. The aim of this review is to describe the pathophysiological relationship of s-HLH in pediatric patients according to infectious microorganisms and their diagnostic association. PubMed, Embase, SCOPUS and LILACS databases were used until May 2022. It was identified an association between s-HLH in pediatric patients and infection by different intracellular pathogens, whose pathophysiology produced similar clinical manifestations such as fever, pancytopenia and hepatosplenomegaly. Therefore, the presence of such findings should be considered to include s-HLH in the differential diagnosis.